Upaya Dinas Sosial Kota Medan Dalam Penanggulangan Gelandangan & Pengemis Sebagai Pemerlu Pelayanan Kesejahteraan Sosial (PPKS) di Pusat Kota Medan - Siburian, Repaldo; Thamrin, Husni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Homeless and beggars are a person or group who does not have a prosperous life whose life is below the poverty line and whose life is on the streets and is included in the Social Welfare Services Providers (SWSP). Factors causing the existence of vagrants and beggars are external and internal factors. External factors arise from the nature and attitude of a person such as being lazy to work, helping with reckless capital, having a physical disability and just following along. Internal factors are those that come from outside a person such as lack of access to employment and the lack of government in overcoming poverty. This research aims to describe and analyze The Medan City Social Service's Efforts In Overcoming Homelessness Beggars As Social Welfare Service Providers (SWSP) In Medan City Center. This type of research is descriptive qualitative with the data sources used are primary data sources by means of observation and interviews. While secondary data by collecting documentation such as books and journals. The results of this study indicate that The Medan City Social Service's Efforts In Overcoming Homlessness And Beggars As Social Welfare Service Providers (SWSP) In Medan City Center through rehabilitation programs are not optimal. This is evidenced by the existence of inhibiting factors such as the lack of infrastructure and suggestions in supporting the rehabilitation of vagrants and beggars carried out by the Medan City Social Service.